Regression of cerebellar tonsillar descent and hydrocephalus after endoscopic third ventriculostomy in a patient with a quadrigeminal arachnoid cyst - Arakawa, Yasuaki (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Posterior fossa arachnoid cysts, including quadrigeminal cistern arachnoid cysts, can occasionally cause compression of the quadrigeminal plate, leading to Sylvian aqueduct stenosis and induction of cerebellar tonsillar descent into the foramen magnum. This, in turn, can result in obstructive hydrocephalus. In such cases, the characteristic of hydrocephalus is generally considered to be hypertensive. CASE DESCRIPTION: We present the case of a 28-year-old female complaining of chronic and progressively worsening headaches following the delivery of her first child. Magnetic resonance imaging revealed marked tri-ventriculomegaly, the arachnoid cyst located in the quadrigeminal cistern, and cerebellar tonsillar descent. Ophthalmoscopy revealed bilateral papilledema indicating a long-standing elevation of intracranial pressure. Endoscopic third ventriculostomy (ETV) was performed successfully and resulted in complete recovery from her headaches and papilledema. Postoperative MRI revealed resolution of ventriculomegaly and cerebellar tonsillar descent, suggesting that the fourth ventricle outlet obstruction was associated with the development of the hydrocephalus in this patient. CONCLUSION: Our case is the first report that a quadrigeminal arachnoid cyst associated with both cerebellar tonsillar descent and hydrocephalus was well treated with ETV. It was indicated that the patient's hydrocephalus and cerebellar tonsillar descent were secondary and synergistic events, caused by the arachnoid cyst located in the quadrigeminal cistern.